A teratology information system in vernacular: Closing an information gap. Issue 15 (24th April 2021) - Patskun, Erika; Yevtushok, Lyubov; Zymak‐Zakutnia, Nataliia; Lapchenko, Serhiy; Akhmedzhanova, Diana; Wertelecki, Wladimir
Abstract: Background: Leading Teratology Information Systems (TIS) arose in major industrial nations and are mostly in English. The prevalence of anglophone speakers in Ukraine is among the lowest in Europe. A TIS in Ukrainian (UTIS) seeks to diminish an information gap concerning teratogens. The process and results related to UTIS are applicable to formulations of other TIS in vernacular languages. Methods: Implementation of a free‐access UTIS and analysis of utilization patterns. UTIS provides access to articles in Ukrainian (AU) which are summaries extracted from leading international TIS and other sources. AU are revised at least tri‐annually. Results: UTIS provides access to over 1, 100 AU accrued since 2016 to the present. The number AU views increased from nearly 30, 000 (2016) to over 80, 000 (2020); the number of visitors increased from 3, 500 to 58, 000 during the same periods. The highest percent of users per urban population (2.09, 1.77, and 1.72) was in Ternopil, Ivano‐Frankivsk, and Kyiv (capital), respectively; the lowest was in Odesa (0.17). Conclusions: UTIS reduced an information gap in Ukraine concerning teratogenic risk factors. The process can be implemented elsewhere relying on generally available local resources.